Data analysis on herbal treatment for chronic kidney disease stage 3 patients in Singapore Thong Chai Medical Institution - Sow, Li Ying (Nanyang Technological University, 2021)
Objective. To identify patient characteristics and core herbs from prescriptions of chronic kidney disease (CKD) stage 3 patients who sought Traditional Chinese Medicine (TCM) treatment in Singapore Thong Chai Medical Institution (STCMI). Methods. Data of patients with CKD from 1 January 2016 to 28 February 2021 were obtained from the electronic medical record system used in STCMI. Analysis of baseline characteristics was performed using R V4.1.1. Analysis of Chinese herbal medicine (CHM) was performed using Gu Jin Yi An Yun Platform V2.3.5 for herbal frequency and properties, cluster analysis, association analysis and core prescription network analysis. Results. 1966 herbal medical prescriptions from 69 CKD stage 3 patients were analyzed. There were twice as many males compared to females. All patients were of Chinese ethnicity and mean age was 72.2 ± 10.5. Core herbs identified were Radix Astragali (Huangqi), Rhizoma Dioscoreae (Shanyao), Poria (Fuling), Eucommiae Cortex (Duzhong) and Spatholobi Caulis (Jixueteng). Radix Astragali was the most frequently prescribed herb among a total of 343 herbs. Conclusions. This study has provided insights on the common herbs which are effective in treatment of CKD stage 3 patients.